Individual reactions to viewing preferred video representations of the natural environment: A comparison of mental and physical reactions. Issue 1 (10th May 2016) - Tsutsumi, Masae; Nogaki, Hiroshi; Shimizu, Yoshihisa; Stone, Teresa Elizabeth; Kobayashi, Toshio
Abstract: Aim: Globally, awareness of the vital link between health and the natural environment is growing. This pilot study, based on the idea of "forest bathing, " or shinrin‐yoku, the mindful use of all five senses to engage with nature in a natural environment, was initiated in order to determine whether stimulation by viewing an individual's preferred video of sea or forest had an effect on relaxation. Methods: The participants were 12 healthy men in their twenties and they were divided into two groups based on their preference for sea or forest scenery by using the Visual Analogue Scale. The participants watched 90 min DVDs of sea with natural sounds and forest with natural sounds while their heart rate variability and Bispectral Index System value were measured by using MemCalc/Tawara and a Bispectral Index System monitor. Results: The participants were divided into two groups of six based on their preference for sea or forest scenery and each indicator was compared between them. Significant differences in a decrease in heart rate, increase in high frequency, and sustained arousal level were observed while viewing the preferred video. These results indicated that the viewing individual's preferred video of sea or forest had a relaxation effect. Conclusion: This study suggests that individual preferences should be taken into consideration for video relaxation therapy.